Comparative Analyses of Inflammatory Response and Tissue Integration of 14 Hyaluronic Acid-Based Fillers in Mini Pigs - Choi MS; Kwak S; Kim J; Park MS; Ko SM; Kim T; Jeong DS; Rhee CH; Yang GH; Son WC; Kang WH (Dove Medical Press, 2021)
Min-Seo Choi,1,* Seongsung Kwak,1,2,* Junhyung Kim,1 Mi-Sun Park,1 Soo Min Ko,2 Taehee Kim,2 Da Som Jeong,2 Chang-Hoon Rhee,3 Gi-Hyeok Yang,1,3 Woo-Chan Son,2 Won-Ho Kang1 1Gwanggyo R&D Center, Medytox Inc, Suwon-si, Gyeonggi-do, Republic of Korea; 2Department of Medical Science, Asan Medical Institute of Convergence Science and Technology, Asan Medical Center, University of Ulsan College of Medicine, Songpa-gu, Seoul, Republic of Korea; 3Osong R&D Center, Medytox Inc, Cheongju-si, Chungcheongbuk-do, Republic of Korea*These authors contributed equally to this workCorrespondence: Won-Ho KangNon-Clinical Development Department, Gwanggyo R&D Center, Medytox Inc, 114 Central Town-Ro, Yeongtong-Gu, Suwon-si, Gyeonggi-do, 16506, Republic of KoreaTel +82 31 8065 8243Fax +82 31 8065 8232Email whkang@medytox.comWoo-Chan SonDepartment of Medical Science, Asan Medical Institute of Convergence Science and Technology, Asan Medical Center, University of Ulsan College of Medicine, 88 Olympic-Ro 43-Gil, Songpa-gu, Seoul, 05505, Republic of KoreaTel +82 2 3010 4051Fax +82 2 3010 4099Email wcson@amc.seoul.krPurpose: Hyaluronic acid (HA)-based dermal fillers have been approved for various clinical indications, both cosmetic and medical. Previous studies that have assessed the performance of HA dermal fillers have primarily focused on evaluating filler durability, and only a few have studied their distribution within the tissues. The present study aimed to compare tissue integration of various types of HA dermal fillers having different clinical indications and varying injection depths.Methods: To examine the local inflammatory response and distribution pattern of 14 HA dermal fillers (six Neuramis [NEU], one Belotero [BEL], three Juvéderm [JUV], and four Restylane [RES]), each product was injected intradermally and subcutaneously at the backs of two male miniature pigs. Histopathological evaluation and visual examination of the tissue sections were conducted 1 and 4 weeks after injection.Results: Mean inflammatory cell infiltration scores tended to be lower in response to fillers from the NEU and BEL series than to those from the JUV and RES series after intradermal and subcutaneous injection. Furthermore, the inflammatory response to fillers with higher physicochemical properties specifically designed for injection into deeper layers of the skin tended to be slightly higher than those designated for injection into more superficial layers. There was no significant difference in tissue integration according to clinical indication and injection depth, although fillers from the NEU and BEL series exhibited better tissue integration than those from the JUV and RES series.Conclusion: Our findings not only suggest that the local inflammatory response and tissue integration differ across HA dermal filler products, but also that these parameters could vary according to the recommended clinical indication and injection depth of the products.Keywords: histopathology, inflammatory response, HA filler, soft tissue augmentation, tissue integration